Identify abnormalities in resting-state brain function between first-episode, drug-naive major depressive disorder and remitted individuals: a 3-year retrospective study. Issue 11 (1st August 2018) - Yang, Chunxia; Zhang, Aixia; Jia, Aixiang; Ma, Jack X.; Sun, Ning; Wang, Yanfang; Li, Xinrong; Liu, Zhifen; Liu, Sha; Xu, Yong; Zhang, Kerang
Abstract : This study aims to identify and characterize neurobiological markers for major depressive disorder (MDD) from resting-state brain functional MRI. We examined the abnormality in the regional homogeneity (ReHo) and amplitude of low-frequency fluctuation (ALFF) in first-episode, drug-naive major depressive disorder (fMDD), and remitted major depressive disorder (rMDD) and correlated these fluctuations with clinical markers of MDD. We conducted a retrospective study and reviewed the medical records of 43 patients with fMDD. Overall, 13 of the 43 patients who had at least 3 years of follow-up care and the 17-item Hamilton Depression rating scale less than 7 took no antidepressants for more than half a year at the end of the 3-year follow-up. We further chose a group of 14 healthy controls matched for age, sex and education level with patients with rMDD. Multiple comparison analysis was performed for ALFF and ReHo. The statistical significance level was set at P value of less than 0.05. We examined whether there were differences among the three groups in the whole-brain ALFF and ReHo during resting state. Compared with healthy controls, patients with fMDD showed significant decrease of ReHo in the right anterior lobe of cerebellum and significant increase of ReHo in the right inferior temporal gyrus, and significant decrease of ALFF in the left inferior parietal lobule and right caudate nucleus. Compared with patients with rMDD, those with fMDD showed significant increase of ReHo in the right fusiform gyrus and the left middle temporal gyrus, and significant increase of ALFF in the right superior temporal gyrus. Compared with healthy controls, patients with rMDD showed significant increase of ReHo in the right supramarginal and significant decrease of ReHo in the right precuneus, and significant decrease of ALFF in the right lingual gyrus and in the left superior frontal lobe. Only patients with fMDD showed the relatively robust increase in intrinsic activity of temporal gyrus. The temporal gyrus may play a critical role in depressive symptomatology. Abnormal right fusiform gyrus, left middle temporal gyrus, and right superior temporal gyrus alterations were present only in patients with rMDD but not in patients with fMDD, indicating that these alterations may be a therapeutic target for MDD. Abnormal right supramarginal, right precuneus, right lingual gyrus and left superior frontal lobe alterations were present only in patients with rMDD and not in healthy control, and thus may be used as a state marker of MDD.